1931 N.D. Laws 305-06 - (:unkn) unknown (My University, 1931)
Ch. 178, §§ 1-2: Prohibited selling, giving, loaning, furnishing, or delivering a machine gun, submachine gun, automatic rifle, or bomb (without a license). Punishable by imprisonment up to 10 years and/or fine up to $3,000.
Keywords: MACHINE GUN RESTRICTION